नारीवाद र तिन घुम्ती उपन्यासमा नारीवादी चिन्तन (Narivad ra Tin Ghumti Upanyasma Narivadi Chintan) - Adhikari अधिकारी, Laxmisharan लक्ष्मीशरण (Janapriya Journal of Interdisciplinary Studies, 2017)
Not Available. Janapriya Journal of Interdisciplinary Studies, Vol. III (December 2014), Page: 62-72